Broccoli extract improves high fat diet-induced obesity, hepatic steatosis and glucose intolerance in Wistar rats. (August 2019) - Aranaz, Paula; Navarro-Herrera, David; Romo-Hualde, Ana; Zabala, María; López-Yoldi, Miguel; González-Ferrero, Carolina; Gil, Ana Gloria; Alfredo Martinez, J.; Vizmanos, José Luis; Milagro, Fermín I.; González-Navarro, Carlos J.
Graphical abstract: Highlights: Broccoli extract (BE) significantly reduces the fat content in C. elegans . BE supplementation reduces body weight gain and food efficiency in Wistar rats. BE reduces visceral fat accumulation and improves glucose homeostasis. BE decreases liver steatosis by increasing lipid oxidation and reducing lipogenesis. Abstract: Brassicaceae contain bioactive compounds with potential positive effects on metabolic syndrome. Here, we evaluated the eventual anti-obesity properties of an ethanolic broccoli extract (BE), selected by a tested ability to reduce Caenorhabditis elegans fat content. Two doses (14 and 140 mg/kg animal) of BE were evaluated in a diet-induced obesity (DIO) Wistar rat model. After 10 weeks of BE supplementation, animals exhibited reduced body weight gain and food efficiency, decreased atherogenic index of plasma and improved glucose tolerance in comparison with non-supplemented rats. BE also reduced the retroperitoneal fat mass and adipocyte size, all associated to down-regulation of Cebpa, Srebp1, Fasn and Adipoq expression in adipocytes. Finally, BE significantly decreased liver steatosis, accompanied by the up-regulation of Acot8 and Acox1, and the down-regulation of Fasn, Fatp4 and Srebf1 expression in hepatocytes. Our data provides new knowledge about the potential role of broccoli components in the prevention of metabolic syndrome.